Review of Heat and Moisture Transfer Models of Fire-Protective Clothing - Rochak Rathour; Azharul Islam; Apurba Das; R. Alagirusamy (Tekstilec)
This paper presents a comprehensive review of previously published research on heat and moisture transfer models applied to fire-protective clothing, which is crucial for ensuring firefighter safety and comfort. By analysing experimental data and numerical simulations from various studies, this review paper tries to explore the intricate interactions between heat, moisture and textile materials. It provides insight into the performance and design optimisation of such clothing, elucidating the dynamic behaviour of heat and moisture transfer within fabric layers. The research results offer valuable guidelines for enhancing protective efficacy while maintaining wearer comfort. This review advances our understanding of fire-protective clothing and lays the groundwork for future innovations in firefighting gear design and material selection.